Karyomaps of cultured and cryobanked Litoria infrafrenata frog and tadpole cells - Mollard, Richard (Data Brief, 2018)
These data and analyses support the research article “Culture, cryobanking and passaging of karyotypically validated native Australian amphibian cells” Mollard (2018) [1]. The data and analyses presented here include: (1) three additional karyomaps of cells from the cryobanked and passaged frog and tadpole species Litoria infrafrenata; and (2) combined short-to-long arm ratios of the four karyomaps measured from each respective animal here and in Ref [1].